ASPECTS OF IMPROVING THE METHODOLOGY FOR DEVELOPING SOCIAL COMPETENCIES - Hasanova Makhmuda Tikhtayevna (Bright Mind Publishing, 2025)
Based on our rich history, it is safe to say that this land has given the word many great scientists: scholars, politicians and historians, heroes and military learders, statesmen and world learders. Many foundations of religious and secular sciences were createdand perfected on this blessed land.
Keywords: History, great scientists, scholars, politicians, historians, heroes, military leaders, statesmen, world leaders, religious sciences, secular sciences, cultural heritage, legacy.